Evaluation of onion cultivars for bulb production in the submédio São Francisco region - D'Oliveira, Lúcio Osório Bastos; Aguiar, Paulo Anselmo A.; Assunção, Marcos Vinicius (Pesquisa Agropecuaria Brasileira, 2014)
Five onion (Allium cepa L.) cultivars were evaluated in six diferent times under the "submédio São Francisco" climatic conditions in the Northeast of Brazil. Treatments were disposed in a randomized complete block design, in a split-plot arrangement with four replications. In the whole plots were alocated the cultivars Pera IPA-1 - Baia do Cedo M(J-IV); Pera IPA -2 - Composto (M(J-IV); Baia Triunfo - Seleção Verão (M(J-IV); Roxa do Barreiro M(J-III) and Texas Grano 502, and in the subplots the following planting date: E1 (12.23.1980), E2 (1.8.1981), E3 (1.23.1981), E4 (2.8.1981), E5 (2.23.1981) and E6 (3.10.1981). The analysis of variance for yield showed F not significant for cultivars and significant for planting time. The average yield of bulbs varied among planting times from 11.7 to 18.3 t/ha, being E3 (1.23.1981) and E4 (2.8.1981) the best planting time. However, these planting time may vary from year to year, according to the climatic conditions, mainly rainfall pattern.